(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2025)
Abstract This article presents recent findings on state intervention in the design of public policies directed toward the care of children in situations of social vulnerability. Drawing on social history with a gender perspective, it examines the political and social context of the city of Neuquén from the 1970s to 2013, with the aim of identifying possible transformations as well as the social actors involved in caregiving work. Keywords: Public policies – Work – Care – Childhood – Gender – History